Different care mode alter composition and function of gut microbiota in cerebral palsy children - Lyu, Jinli; Zhang, Xiaowei; Xiong, Shenghua; Wu, Hui; Han, Jing; Xie, Yongjie; Qiu, Feifeng; Yang, Zhenyu; Huang, Congfu (Frontiers in Pediatrics, 2024)
Specialized care is essential for the recovery of children with cerebral palsy (CP). This study investigates how different care modes impact the gut microbiota. Fecal samples from 32 children were collected, among whom those cared for by family (n=21) were selected as the observation group, and those cared for by children's welfare institutions (n=11) were selected as the control group (registration number of LGFYYXLL-024).The gut microbiota profiles were analyzed. There was no significant difference in the α-diversity of the gut microbiota and the abundance at the phylum level. However, at the genus level, the observation group showed a significant increase in the abundance of butyrate-producing bacteria Bacteroides and Lachnospiracea incertae sedis (P<0.05), and a significant decrease in the abundance of opportunistic pathogens Prevotella, Clostridium cluster IV, Oscillibacter, and Fusobacterium (P<0.05).Additionally, lipid metabolism, carbohydrate metabolism, transcription, cellular processes and signaling, and membrane transport were significantly upregulated in the observation group. Lipid metabolism was positively correlated with Bacteroides and Lachnospiracea incertae sedis, indicating a positive impact of the family-centered care mode on bacterial metabolism processes. This study highlights that the family-centered care mode had a positive impact on the composition and function of the gut microbiota.The study provides valuable insights into the relationship between care mode and gut microbiota, which can inspire the development of interventions for cerebral palsy.